Hepcidin is localised in gastric parietal cells, regulates acid secretion and is induced by Helicobacter pylori infection - Schwarz, Peggy; Gerloff, Andreas; Feick, Peter (Gut, 2011)
Backgrounds and aims Hepcidin is an antimicrobial peptide and the central regulator of iron metabolism. Given that hepcidin was shown to be expressed in a variety of extrahepatic tissues and that stomach plays a role in iron absorption and in defence against infections, this study analysed the importance of hepcidin in the stomach. Methods Expression and localisation of gastric hepcidin was studied by quantitative RT-PCR, western blot, immunofluorescence and in situ hybridisation. Regulation of gastric hepcidin expression was analysed both in vitro and in vivo. Hepcidin wild-type (WT) and knockout (KO) animals were used to determine the impact of hepcidin on gastric bacterial overgrowth as well as gastric acid secretion. Results Hepcidin was abundantly expressed in the gastric fundus and corpus of all tested species. Treatment of AGS cells with ferric nitrilotriacetate solution downregulated hepcidin expression levels, while desferroxamine, interleukin 6 and Helicobacter pylori infection upregulated it. In humans, gastric hepcidin expression was elevated during H pylori infection and normalised after successful eradication. Gastric hepcidin is localised in parietal cells that are indispensable for gastric acid secretion. Comparisons of WT and hepcidin KO mice revealed that acid secretion in hepcidin-deficient mice is markedly reduced and is associated with gastric bacterial overgrowth, expression changes in multiple factors involved in acid secretion (Atp4a, Cck2r,Gas, Sst and Sst2r) and with reduced circulating gastrin levels. In WT mice, pantoprazole activated and histamine downregulated hepcidin expression levels. Conclusions Hepcidin is a product of parietal cells regulating gastric acid production and may contribute to development of gastric ulcers under stress conditions.
Gesehen am 30.05.2018